2009
DOI: 10.1186/1477-7827-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 is elevated in midtrimester amniotic fluid prior to the development of preeclampsia

Abstract: Higher amniotic fluid MMP-2 and TIMP-2 levels are found in women who eventually develop preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Also, mean amniotic TIMP-2 levels are higher in women who developed a hypertensive disorder compared to normotensive women (Lavee et al, 2009; Montagnana et al, 2009). A decrease in ECM remodeling could play a role in HELLP syndrome.…”
Section: Mmps In Pregnancy and Preeclampsiamentioning
confidence: 95%
See 2 more Smart Citations
“…Also, mean amniotic TIMP-2 levels are higher in women who developed a hypertensive disorder compared to normotensive women (Lavee et al, 2009; Montagnana et al, 2009). A decrease in ECM remodeling could play a role in HELLP syndrome.…”
Section: Mmps In Pregnancy and Preeclampsiamentioning
confidence: 95%
“…A study enrolling 133 women showed no statistical difference in MMP-2 levels between patients with gestational HTN and normotensive controls (Lavee et al, 2009) or between PE and normotensive women (Galewska et al, 2008). Another study enrolling 83 pregnant women showed no difference in pro-MMP-2 levels (Palei et al, 2008).…”
Section: Mmps In Pregnancy and Preeclampsiamentioning
confidence: 96%
See 1 more Smart Citation
“…Both have been found in amniotic fluid and the concentrations of both zymogen and inhibitor free active forms of MMP9 are elevated in the amniotic fluid of women with pPROM 133144;150-153 We have previously reported that amniotic fluid TIMP2 concentrations are lower in women with spontaneous labor (term and preterm), with intact or ruptured membranes, regardless of the microbial status of the amniotic cavity, than in women not in labor 133. A decrease in TIMP2 amniotic fluid concentration is thought to favor MMP activity promoting extracellular matrix degradation, which has been associated with labor 152.…”
Section: Commentmentioning
confidence: 99%
“…MMP2 is a constitutive enzyme, while MMP9 is inducible in response to infection. 140 Both have been found in amniotic fluid [141][142][143][144][145] and the activity and concentration of MMP9 is increased in the amniotic fluid of women with preterm labor and intact membranes, as well as in women with preterm PROM. 141;143 We have previously reported that amniotic fluid TIMP2 concentrations are low in women with spontaneous labor (term and preterm), with intact or ruptured membranes, regardless of the microbial status of the amniotic cavity.…”
Section: Single Locus Analysis For Mothersmentioning
confidence: 99%